Mainstreaming Human Rights in the Governance of HIV/AIDS Response in Indonesia: A Study of Children with HIV/AIDS in Jakarta and Surakarta - PRABANDARI, ATIN; RIMBAWATI, PUTRI RAKHMADHANI NUR; DINARTO, DEDI; ARDHANI, IRFAN; KURNIAWAN, MUHAMMAD DIAZ; IRSADANAR, RAFYOGA JEHAN PRATAMA (Universitas Muhammadiyah Yogyakarta, 2018)
This research aims to compare the advocacy model of Children Living with HIV/AIDS (CLWH) informal– non-professional and formal–non-professional network, represented by Lentera Anak Surakarta (LAS) and Lentera Anak Pelangi Jakarta (LAP) respectively. The characterization of the network was adapted from Lhawang Ugyel conceptual framework on four types of social network based on their personnel types and formality. Meanwhile, the comparison was made under the metric of 3 advocacy channels; legislation, political and mobilization process. This research found out that LAS informalâ€”non-professional advocacy model reflected a more dominant usage of law and political channel compared to LAP formalâ€”non-professional model since LAS was rising from marginalized society hence they need well lobbying politically and involving in legal drafting. Meanwhile, LAP had shown a more systematic maneuver on the socialization and mobilization channel of advocacy. This was because LAP was formally driven by academia spectrum that could establish methodical movements of CLWH advocacy; thus the engagement with policymaker was less prioritized, even though it was still an essential element of its advocacy.